Persepsi Masyarakat tentang Tokoh Joker dalam Film Joker (Studi Kasus pada Penonton Film di Studio 21 Makassar Town Square) - Armadi Jaya Putra; Pramudita Budi Rahayu (Journal of Communication Sciences (JCoS), 2020)
At the end of 2019 the people of Makassar were presented with a film with a background story and production from the United States with the title "JOKER". The Joker is an antagonist who is usually portrayed in a clown costume or make up with a psychological disorder who is also the enemy of the super hero Batman. The Joker in this film becomes the main character by telling his dark past life to become a Joker. Researchers see this film as very interesting to be examined when the main character in this film has an antagonistic role played in Indonesia, especially the city of Makassar. This study aims to reveal the public's perception of the Joker character in the Joker film and the factors that influence this perception. This study uses a qualitative descriptive method which is analyzed intensively and continues continuously to obtain the desired data. The results of this study explain that the Joker film is still less attractive to the public, especially the city of Makassar, because the contents of this film have more entertainment functions than informative and educational. However, this film also teaches us to always do good to everyone and not occasionally oppress others if we don't want to be hated or hurt. This perception is based on the inhibiting factors of society from watching the Joker film, namely Ecology, Technology, and Social. While the driving factors for the community in watching the Joker film are Attention, Interests and Mood. The research recommendation for film producers is to be even more creative in packaging this Joker film, and to provide more educational moral messages.